Socio-Demographic Characteristics and Prevalence of Gender-Based Violence Among Female Sex Workers in Rural Areas, South Africa - Jonas, Phumla; Mokgatle, Mathildah; Mokwena, Kebogile; Hoque, Muhammad (Al-Sihah: The Public Health Science Journal, 2024)
In rural areas, a dearth of health care support services, lack of legal protection, and widespread stigma can lead to increased cases of violence and exploitation, making it increasingly difficult for female sex workers to seek help or escape situations of abuse. The aim of this study was to investigate the prevalence of gender-based violence (GBV) among female sex workers (FSWs) in the Westrand District area of Mogale, South Africa. This was a descriptive, quantitative study conducted among 383 FSWs who were selected using a systematic random sampling technique. Data were collected using self-administered questionnaires. About half of the FSWs (45%) were between the ages of 25 and 35. Most of the FSWs were single (91%), and half of them (54%) had completed only secondary education. Results showed that two-thirds of the FSWs (67%) experienced GBV. More than two-thirds (70%) had been belittled, 60% reported being insulted, 43% of FSWs had experienced forced vaginal sex, and another 40% had experienced forced anal or oral sex. Among those who did not report the violence, 18% indicated financial reasons, followed by personal choice. GBV is pervasive among FSWs in Mogale City and hinders HIV prevention efforts as well as access to justice and treatment. An integrated, multi-sectoral GBV strategy that addresses structural risks is required to improve safety and promote access to care and justice.